Transcriptional analysis of wheat seedlings inoculated with Fusarium culmorum under continual exposure to disease defence inductors - Antalová, Zuzana; Bleša, Dominik; Martinek, Petr; Matušinsky, Pavel (PloS one, 2020)
A facultative parasite of cereals, Fusarium culmorum is a soil-, air- and seed-borne fungus causing foot and root rot, fusarium seedling blight, and especially Fusarium head blight, a spike disease leading to decreased yield and mycotoxin contamination of grain. In the present study, we tested changes in expression of wheat genes (B2H2, ICS, PAL, and PR2) involved in defence against diseases. We first compared expression of the analysed genes in seedlings of non-inoculated and artificially inoculated wheat (variety Bohemia). The second part of the experiment compared expression of these genes in seedlings grown under various treatment conditions. These treatments were chosen to determine the effects of prochloraz, sodium bicarbonate, ergosterol, aescin and potassium iodide on expression of the analysed defence genes. In addition to the inoculated and non-inoculated cultivar Bohemia, we additionally examined two other varieties of wheat with contrasting resistance to Fusarium sp. infection. These were the blue aleurone layer variety Scorpion that is susceptible to Fusarium sp. infection and variety V2-49-17 with yellow endosperm and partial resistance to Fusarium sp. infection. In this manner, we were able to compare potential effects of inductors upon defence gene expression among three varieties with different susceptibility to infection but also between inoculated and non-inoculated seedlings of a single variety. The lowest infection levels were detected in the sodium bicarbonate treatment. Sodium bicarbonate had not only negative influence on Fusarium growth but also positively affected expression of plant defence genes. Expression of the four marker genes shown to be important in plant defence was significantly affected by the treatments. The greatest upregulation in comparison to the water control was identified under all treatments for the B2H2 gene. Only expression of PAL under the ergosterol and prochloraz treatments were not statistically significant.
Keywords: Plant Diseases; Sodium Bicarbonate; hydrogenuhličitan sodný; Fusarium; stanovení celkové genové exprese; Seedlings; Triticum; semenáček; Disease Resistance; Gene Expression Profiling; pšenice; odolnost vůči nemocem; nemoci rostlin